Axial test of full-scale columns strengthened with jacket section. Issue 19 (8th October 2020) - Hwang, Yong-Ha; Yang, Keun-Hyeok; Mun, Ju-Hyun
Abstract : This study examines the effect of different arrangements of transverse reinforcement in the jacket section on the axial performance of full-scale reinforced-concrete columns strengthened with a seismic section enlargement approach. For the jacket section with seismic details, overlapped channel-shape bars and prefabricated bar units were designed as the closed peripheral hoops, and V-ties or segmented cross-ties were used for the supplementary transverse reinforcement. For the compressive tests of full-scale strengthened columns with a 750 mm square section, a steel loading frame with a 40 000 kN capacity hydraulic jack was specially devised. Test results showed that the strengthened columns without supplementary V-ties in the jacket section possessed lower ductility capacity when compared with that of the existing non-seismic column. At the same level of transverse reinforcement index, the axial ductility ratio obtained from the present full-scale columns was typically lower than that compiled from the scaled-down column specimens with a square section of 200–300 mm. However, the strengthened column with prefabricated bar unit hoops including supplementary V-ties exhibited good ductility, which was comparable to the axial ductility ratios obtained in scaled-down columns, although a size effect potentially induced a more rapid decreasing rate at the descending branch of the stress–strain relationship of the concrete.